Fluctuating or progressive hearing loss in the middle-to-high frequencies may suggest the neurotologic endotype of perilymphatic fistula without antecedent traumatic events - Matsuda, Han; Maeda, Yukihide; Kitahara, Tomoyasu; Sawada, Masafumi; Kudo, Hiroe; Sakamoto, Kei; Takayama, Atsuya; Ikezono, Tetsuo (Frontiers in Neurology, 2025)
BackgroundIdiopathic sudden sensorineural hearing loss (ISSNHL) is a common clinical condition. Recent studies indicate that approximately 20% of ISSNHL cases may involve perilymphatic fistula (PLF). The detection of Cochlin-tomoprotein (CTP) in middle-ear lavage samples confirms the diagnosis of PLF.Aims/ObjectivesTo clarify the clinical characteristics of inner ear–related symptoms in patients with PLF who lacked any antecedent traumatic events prior to symptom onset.Materials and methodsWe retrospectively reviewed clinical records and CTP test results in 769 cases from 70 hospitals in Japan.ResultsAmong these cases, 204 had no history of antecedent events. CTP-positive findings were more frequently observed in patients exhibiting fluctuating and/or progressive hearing loss than in those without these symptoms (p < 0.05, Fisher’s exact test). The odds of a positive CTP test did not differ between patients with and without vestibular symptoms, nystagmus, a fistula sign, a popping sensation, or streaming water–like tinnitus (p > 0.05, Fisher’s exact test). The CTP positivity rate was highest in patients with a high-frequency sloping audiogram.Conclusions and significanceFluctuating or progressive hearing loss in the middle-to-high frequencies may reasonably suggest PLF in the absence of antecedent traumatic events.